Political decentralization Under the Constitution of the Republic of Iraq for 2005: An analytical study - طالب, مصدق عادل; الجزائري, مروج هادي (Journal of Legal Sciences, 2020)
This research deals with political decentralization under the Constitution of the Republic of Iraq in 2005 in terms of reviewing the concept of the term and its pillars, as well as setting boundaries with other terms that converge with it such as administrative decentralization and autonomy. In order to answer an important question related to the evaluation of the effectiveness of the introduction of this system by the Iraqi legislator, and to indicate the obstacles that prevented the implementation of this system despite the passage of nearly a decade to the entry into force of the Iraqi Constitution, and then propose a road map to complete the construction of this system and its pillar.